Agenda Setting Pemerintah Kabupaten Badung dalam Kebijakan New Normal Tourism COVID-19 - Angelya, Putu Jasisca; Erawan, I Ketut Putra; Jayanti Mertha, A.A.Sagung Mirah Mahaswari (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
The New Normal Tourism policy made by the local government of Badung Regency has become a policy in the midst of the Covid-19 pandemic. Agenda Setting Theory by John W. Kingdon which is used to dissect research and examine agenda setting that occurs in the local government of Badung Regency. In this study using qualitative research methods through interviews with several sources and archives obtained from the DPRD Badung Regency. The results of this study the authors get as follows: First, the New Normal Tourism policy only becomes a government discourse in society. Second, there is no pressure from the government or non-government in following up on the New Normal Tourism policy. Third, the highest power is held by the central government in dealing with the New Normal Tourism policy in the local government of Badung Regency.